Influence of metabolites of microorganisms from permafrost on the synthesis cytokines by human peripheral blood mononuclear cells in vitro - S. S. Kolyvanova; L. F. Kalenova (Медицинская иммунология, 2021)
Permafrost is a unique ecosystem characterized by consistently negative temperatures. It has been shown that microorganisms can be there in a state of hypometabolism or anabiosis during geological time. It is known that microorganisms occupy a wide habitat due to the presence of multifunctional systems of adaptation and communication. One of the manifestations of these systems is the production of secondary metabolites (MBs), which include signaling molecules that do not have strict species specificity. The biological activity of signaling molecules largely depends on the number of bacterial cells and the temperature of their cultivation.In this work we used secondary MBs of Bacillus sp. from Permafrost obtained at different temperatures of microorganism cultivation (at -5 °C – “cold” MBs and at 37 °C – “warm” MBs) in doses of 0,05 × 106 (small dose) of microbial cells (m.cl.) in ml of saline or 500 × 106 (high dose) m.cl./ml. The influence of MB of Bacillus sp. for the TNFα, IL-1β, IL-8, IL-2, IFNγ, IL-4 and IL-10 production by human peripheral blood mononuclear cells (MNC) in supernatants of 24-hour cell cultures was estimated by ELISA whith using the “VectorBEST” test system (Russia) on a LUCY-2 (ANTHOS) spectrophotometer (Austria).It was found that the activity of synthesis by human MNC of the main spectrum of cytokines significantly increased (p < 0.01 for all indicators) under the influence of MB Bacillus sp. regardless of the temperature of their cultivation and the dose of bacteria. The exception was IL-8, the level of which under the influence of a high dose of “warm” MBs didn’t differ from the control. Compared to PHA the cytokines synthesis by MNC depended on the dose and the temperature of obtaining of MBs. Thus, under the influence of “warm” MBs the level of TNFα was significantly lower than its level under the influence of PHA regardless of the dose. Regardless of the temperature of obtaining metabolites the level of IL-8 under the influence of metabolites from a dose of 500 × 106 m.cl. was reduced relative to the PHA group. Comparison of the influence of “warm” and “cold” MBs of Bacillus sp. showed that small doses of “cold” metabolites to a greater extent stimulate the synthesis of pro-inflammatory cytokines (TNFα, IL-1β, IL-8, IFNγ). High doses of “heat” metabolites of Bacillus sp. to a greater extent they activate human MNCs for the synthesis of anti-inflammatory cytokines (IL- 4 and IL-10). Considering that TNFα, IL-1β and IL-10 are cytokines of systemic action and are responsible not only for the activation of the immune system, but also for the mobilization of other regulatory systems of the organism, it can be assumed that the secondary metabolites of microorganisms from Permafrost will be efficient as a substrate for the development of new immunomodulators and adaptogens in the future.